Pemahaman Jamaah Tablig terhadap Ayat-Ayat Dakwah dan Implikasinya terhadap Konsep Khurūj dan Jawlah - Abdul Hakim Wahid; Ahmad Muhaimin (Himpunan Peminat Ilmu-Ilmu Ushuluddin (HIPIUS), 2020)
This article aim to disclose and understand the concept of dakwah implemented by the Dakwah movement in the Kebon Jeruk mosque, and to know how their understanding of the verses referred as evidence arises some concepts of dakwah done such as khurūj, and the verses that are a foothold to preach with the concept of Jawlah. Based on the results of the research, concluded that the verses of Dakwah which are referenced and understood by the jamaah Tabligh are essentially the same as most other dakwah movements. In understanding some verses that are then used as the basis of their arguments, it can be said that they are more looking at the literal-textual aspect, rather than the substantive-contextual meaning. And for the emergence of the concept of Dakwah with the name Khurūj and Jawlah, is a representation of the Prophet and his companions Dakwah when spreading Islam in the Mecca, and not based on Qur’an.